Maize symbology in ancient andean culture: resistance and identity of the andean man - Arroyo Aguilar, Sabino (2019)
All millenary civilizations of agrarian origin continue to preserve myths, stories and icons that represent their domesticated products. These products contribute to human nutrition and constitute symbols of social identity and cultural legitimacy.